PRAWO RZYMSKIE – SKŁADNIK ANGIELSKIEJ DOKTRYNY I PRAKTYKI PRAWA NARODÓW? - Marzec, Łukasz (Zeszyty Prawnicze, 2017)
ROMAN LAW AS A PART OF THE ENGLISH DOCTRINE AND PRACTICE OF THE INTERNATIONAL LAW Summary This paper presents views on the role played by Roman Law as a factor in creating the roots of international law which developed within the English legal doctrine from the 16,h to the 19th century. In addition, it exemplifies applications of the institutions of Roman law in international legal practice. The general theory discounts the influence of Roman law on the British system of law. This, however, should be reviewed, as the evidence shows that Roman law has always played a vital role in the English legal system (e. g. Courts of Chancery, Admiralty, Constable and Marshall, Ecclesiastical Courts, Doctors’ Commons organisation). The Roman influences on the doctrine of English international law (Gentilis, Zouche, Duck, Wiseman, Westlake, Maine, Phillimore) indicate a positive, or even enthusiastic attitude towards the use of Roman law as a source of international law. One of the public branches where English practitioners and theorists of civil law could always find employment was in HM Foreign Service, which had a strong need for lawyers qualified in Roman law who were often educated and trained at English universities. One of the earliest authors describing the use of the theory and practice of Roman law in international law was Alberigo Gentili. Although he was Italian, his professional life and career was bound to England as both a Regius Professor at Oxford University and as a legal counsellor for the Privy Council. He gained much prominence and his works on international law, De Jure Belli, De Legationibus and Advocationis Hispanicae have become frequently quoted in the theory of international law. Another Oxford Regius Professor, and a judge in the Admiralty Court, Sir Richard Zouche, together with Gentili and Grotius, is regarded as the father of international law. Among his many works, Jus inter Gentes and Juris et Judicii Fecialis illustrate the influences of Roman law on the developing theory (and practice) of international law. The Roman ideas are particularly visible in Jus Inter Gentes, where Zouche had used the Roman systematic of status, dominium., delictum and judicium to classify and explain international law theory. Another 17th century civil lawyer, Sir Robert Wiseman, in The Excellency o f the Civil Law above all other Human Law glorifies the Roman law as universal law for all nations, applicable to many international debates. One of the most famous British civilians and international law experts, Sir Henry Maine considered the Roman law as an important resource and element of the 19th century doctrine of international law. According to Sir Robert Phillimore, the Roman law could be used in the controversies between independent States. As an example he described the cases between the USA and Spain concerning navigation in the Mississipi River, boundary disputes and arbitration. He proposed application of the Roman law to numerous cases concerning overseas properties. Apart from theory, hundreds of international cases bear traces of successful application of the Roman law to resolve situations when there was no actual law institution to bridge the legal divide. This paper presents five international cases in which an important role was played by Roman law. Arbitration of the Behring Sea dispute in 1893, where the UK and the USA argued about the UK’s right to hunt seals outside the three miles boundary area of the Pribilof s Isles. Both sides used arguments based on Roman law. The Americans view was that seals born on the isles would always return to the shore, not losing animus revertendi of Roman law, thus not becoming res nullius and not subject to „occupation” by the UK fishermen. The British delegates claimed that the seals were born ferae naturae (another Roman law category), and so everyone should be entitled to hunt them. The Alaskan Boundary Tribunal proceedings of 1903 declared that Roman law rules, as a source of international law, should take precedence over the rules of common law. During the Venezuelan arbitration before the Hague Tribunal in 1903, the opponents dealt with many Roman law institutes (like pignus> hypotheca, cessio bonorum, negotiorum gestio and others), trying to adjust them to their actual position. In 1910 the Arbitration Tribunal concerning fishing on the North Atlantic coast allowed the Roman definition of servitude and attempted to treat a state’s territory as a Roman property. The last case dealt with in the paper is the famous Indian Oil Corp. Ltd v. Greenstone Shipping dispute of 1987. The British judge applied the Roman law of confusioy declaring that no previous common law precedent was applicable to this case in which crude oil had been accidentally mixed on board the tanker. Taking into consideration these examples, one may draw the conclusion that Roman law has been an inspiration for European lawyers, as well as English common lawyers, in both the theory and practice of international law.